2016
DOI: 10.1002/2015gc006207
|View full text |Cite
|
Sign up to set email alerts
|

Inference of the viscosity structure and mantle conditions beneath the Central Nevada Seismic Belt from combined postseismic and lake unloading studies

Abstract: We test whether a single depth‐dependent Newtonian viscosity structure can be found to explain measured surface deformation in Western Nevada from two separate loading events: tectonic loading from a series of seven historic earthquakes in the Central Nevada Seismic Belt and nontectonic loading from the formation and evaporation of co‐located Pleistocene‐aged Lake Lahontan. Rheologic studies are generally plagued with nonuniqueness issues due to the limitations of observational constraints. Here, we reduce non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 64 publications
2
8
0
Order By: Relevance
“…This minimum viscosity is 90 comparable to the values obtained for the Lake Bonneville region but might extend over a larger 91 depth range (Bills et al, 2007). Post-seismic studies from Lake Lahontan find slightly lower 92 viscosities over the same depth range but overlap within uncertainty with the lake rebound 93 obtained viscosities (Dickinson et al, 2016). 94 95 These Basin and Range sub-lithospheric viscosity estimates are significantly lower than global 96 average estimates at this depth of ~5 x 10 20 Pa s, obtained from observations derived from 97 postglacial rebound (Peltier et al, 2015).…”
supporting
confidence: 68%
“…This minimum viscosity is 90 comparable to the values obtained for the Lake Bonneville region but might extend over a larger 91 depth range (Bills et al, 2007). Post-seismic studies from Lake Lahontan find slightly lower 92 viscosities over the same depth range but overlap within uncertainty with the lake rebound 93 obtained viscosities (Dickinson et al, 2016). 94 95 These Basin and Range sub-lithospheric viscosity estimates are significantly lower than global 96 average estimates at this depth of ~5 x 10 20 Pa s, obtained from observations derived from 97 postglacial rebound (Peltier et al, 2015).…”
supporting
confidence: 68%
“…While estimates of the viscosities of the lower crust and upper mantle differ somewhat among the various studies [ Thatcher and Pollitz , ], the interpretation of the uplift anomaly as a long‐lived viscoelastic response seems to be agreed upon. More detailed modeling with realistic rheological properties that integrates coseismic, early, and later postseismic deformation suggests that a symmetric uplift response in the later postseismic period is expected, that the deformation source is mantle flow immediately beneath the crust, and that the mechanical lithosphere is ~40 km deep [ Thompson and Parsons , ; Dickenson et al , ].…”
Section: Resultsmentioning
confidence: 99%
“…There is the additional complication that afterslip must be accounted for in post-seismic studies (Ingleby and Wright, 2017), but in general, the changing deformation rates observed during an earthquake cycle suggest that the Earth either follows a power-law rheology (Freed and Burgmann, 2004;Freed et al, 2006), or a rheology comprising several different 820 relaxation times (Pollitz, 2005;Hetland and Hager, 2006). Is there a single rheological law that can explain GIA, post-seismic deformation, intra-plate deformation, and deformation in response to sediment or lake loading (Gilbert, 1890;Dickinson et al, 2016)? It is clear that the Earth behaves differently over different timescales (Burgmann and Dresen, 2008;Watts et al, 2013), and it will be interesting to see how parallel fields of research progress towards quantifying the rheological structure of the solid Earth, and the degree to which the rheology reflects the forcing that is applied.…”
Section: Low Viscosity Regionsmentioning
confidence: 99%